Synergistic co-pyrolysis of polyethylene terephthalate and hibiscus rosa-sinensis: Catalytic mechanisms for optimizing pyrolysis yields - Ahmad Yani; Widya Wijayanti; Mega Nur Sasongko; Slamet Wahyudi; Purbo Suwandono; Musyaroh Musyaroh (South African Journal of Chemical Engineering, 2025)
This study investigated the co-pyrolysis of Polyethylene Terephthalate (PET) and Hibiscus rosa-sinensis (HRS) biomass as a sustainable approach for waste valorization and biofuels production. This study improves both yield and fuel quality by emphasizing HRS's potential as a valuable co-feedstock for sustainably valorising PET waste and producing biofuels. Various PET and HRS weight ratios (100 %, 95 %: 5 %, 90 %: 10 %, 85 %: 15 %, and 80 %: 20 %) were employed at 350 °C pyrolysis temperature.Both the experimental and simulation results indicated that product distribution was significantly affected by HRS. The slight addition of HRS (90:10) had a synergistic effect, yielding a maximum oil output of 538 ml and 393 g (78,6 % yield), exceeding the yield from pure PET pyrolysis. The oil yield indicated that the fuel characteristics were superior at this ratio. The octane number increased to 98, the calorific value remained approximately constant at 46.65 MJ/kg, but viscosity and density exhibited variations. Moreover, the addition of HRS significantly increased and accelerated gas yields, particularly CH₄ and H₂, indicating HRS's catalytic role in facilitating cracking and reforming processes.The catalytic activity of HRS is primarily related to its flavonoid compounds. The flavonoid greatly improves the co-pyrolysis of PET and HRS by encouraging bond cleavage, increasing the formation of oxygenated compounds, making it easier to turn long-chain hydrocarbons into valuable gases, and making the pyrolysis yields better overall in terms of quality and stability. HyperChem simulation results demonstrate alterations in molecular design, polarizability, and energy dynamics, thereby providing a molecular-level understanding of these synergistic effects.